(untitled) (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2025)
CONTEXTUALIZAÇÃO: Although we know that the prevalence of sleep complaints in the general population of Brazil is high and that the sleep of people with musculoskeletal disorders tends to be of poor quality, the prevalence of sleep complaints in the population of patients with musculoskeletal disorders is unknownAlthough we know that the prevalence of sleep complaints in the general population of Brazil is high and that the sleep of people with musculoskeletal disorders tends to be of poor quality, the prevalence of sleep complaints in the population of patients with musculoskeletal disorders is unknown. OBJETIVOS: The aim was to identify the frequency of sleep complaints in individuals undergoing physiotherapeutic care due to musculoskeletal disorders and investigate which are most prevalent in this population. MÉTODOS: We conducted a cross-sectional study that included individuals aged 18 or over with musculoskeletal disorders undergoing physiotherapeutic care. Participants were recruited from physiotherapy clinics in the city of Belo Horizonte. Sociodemographic variables were collected using a pre-structured form, and sleep complaints were collected using the Sleep Complaints Questionnaire. Data collection was carried out online using the Google Forms platform. For data analysis, a descriptive analysis was carried out in which the variables were presented in relation to their measures of central tendency and variability to characterize the sample and present the prevalence of sleep complaints. RESULTADOS: A total of 85 participants with a mean age of 51.4 ± 16.9 years, most women (56.5%) were included in the study. We found that 92.9% of the sample had at least one sleep complaint. The predominant sleep complaints were waking up during the night (70.6%), waking up tired or feeling that sleep was insufficient (49.4%), and nighttime awakenings (45.3%). CONCLUSÕES: Our findings show a high prevalence of sleep complaints in individuals with musculoskeletal disorders who are undergoing physiotherapeutic treatment. These individuals tend to have more discontinuous, fragmented, and non-restorative sleep, which are signs of sleep restriction IMPLICAÇÕES: Our work emphasizes that physiotherapists should consider sleep as part of the prognosis and therapeutic planning. To support this, it is necessary to include sleep-related content in Physiotherapy curriculum, as well as to offer training and courses on the relationship between sleep and pain, sleep and the musculoskeletal system, and how to apply non-pharmacological strategies to improve sleep in patients undergoing physiotherapeutic treatment. Given the high prevalence of sleep disorders, healthcare managers can be encouraged to promote the development of screening and monitoring protocols for sleep in physiotherapy clinics and outpatient settings. Identifying and addressing sleep disturbances can lead to more effective treatments, positively impacting the performance indicators of healthcare services.